THE INFLUENCE OF FINANCIAL AND NON-FINANCIAL COMPENSATION ON TEACHER PERFORMANCE AT MADRASAH TSANAWIYAH NEGERI 1 MUNA - Fadhil Nur Makkaraeng Hasanuddin; Andi Mustika Amin, Uhud Darmawan Natsir, Abdi Akbar Idris, Rezky Amalia Hamka (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to determine the effect of financial and non-financial compensation on teacher performance at the Madrasah Tsanawiyah Negeri 1 Muna. This research variable consists of Financial Compensation and Nonfinancial Compensation as independent variables and Teacher Performance as the dependent variable. This type of research is quantitative which uses primary and secondary data. The population in this study was 40 Madrasah Tsanawiyah Negeri 1 Muna teachers. The sampling technique used was saturated sampling with a sample size of 40 respondents. The data collection technique was carried out by distributing questionnaires to teachers and school principals. The data analysis technique uses multiple linear regression with the help of SPSS version 25 software. The results of this research show that financial and non-financial compensation has a positive and significant influence on teacher performance at Madrasah Tsanawiyah Negeri 1 Muna.